Knowledge Management on Student Centered Learning Methods - Varol, Nurhayat (Academic Conferences Ltd, 2010)
Learning is one of the few things which can not be limited or ignored. It is also a major source that help people to grow up as well as it plays the top role in today's education system. As the life itself is made out of learning, in the classical and the traditional approach of college teaching, most class time is spent with the instructor lecturing and the students listening and watching. The students are mostly passive and there is only one way learning which is from instructor to the students. The overall contribution of the students is very weak in this system. Technical Education Faculty of Firat University in Turkey is training technical teacher for vocational and technical high schools. At the Department of Computer Science Education we have established student centered learning methods since 1998. Some courses such as Computer Aided Education, Expert Systems, Multimedia Systems, Computer Systems, Robotics, Networks, etc. have offered in student oriented learning method and as well as in the traditional approach where the professor was lecturing and students were listening. In the student centered learning methods, the students were distributed into groups where each group has 5 to 6 members. A topic has given to the students that should be presented to the class. The students have organized the teaching methodology themselves. They have used modern teaching tools like projectors, computers using videos, animation, and simulation software. The teaching period have recorded as videos to watch how the course was held by the students. The instructors have evaluated the students considering their knowledge, teaching effectiveness, and their interaction with the audience. The students who have been educated in the student centered learning and traditional learning methods have taken the same final exam. The exam has two parts where in the first part classical and theoretical questions has been asked, the second part of the exam has involved with applying the theoretical information in the laboratories. In this study, the success of the students who are trained in student centered learning and traditional learning methods are analyzed and compared. The role of the knowledge management in the student centered method; weaknesses and strengths of the both methods are discussed and compared. The grades of the students that have been obtained since 1998 at the Computer Science Education Department evaluated and finally some recommendations are offered.
7th International Conference on Intellectual Capital, Knowledge Management and Organisational Learning -- NOV 11-12, 2010 -- Hong Kong Polytechn Univ, Hong Kong, PEOPLES R CHINA
Keywords: student centered learning; method; traditional learning; knowledge management